Comparative Analysis of Water Quantity and Quality in Relation to Vegetation Cover in Himalayan Moist Temperate Forests of Galliyat - Asif Javed; Adnan Saleem Khan; Anwar Qadir; Salman Khan; Salim Shehzad (International Journal of Economic and Environmental Geology, 2016)
The aim of this work was to study the impact of deforestation on water quality and quantity in and around Ayubia National Park-Galliyat, Pakistan. Streams from three vegetation zones (HDZ high density vegetation zones, MDZ moderate density vegetation zones, LDZ low density vegetation zones) were selected for comparative analysis. Altitude, slope and aspects (southern and northern) of three sites were kept constant, whereas deforestation was taken as the only variable. Average discharge rates determined during winter and summer of 2010-11 were found highest for HDZ streams [QBR (0.011 and 0. 1241 m3/sec) and QAR (0.0128 and 0.1287 m3/sec)] followed by MDZ streams [QBR (0.0106 and 0. 1218 m3/sec) and QAR (0.0126 and 0.1284 m3/sec)] and lowest [QBR (0.0045 and 0.0157 m3/sec) and QAR (0.0140 and 0.01284 m3/sec)] for LDZ streams. Similarly, pre- and post-rainfall variations in discharge rates were recorded the highest in LDZ (0.06 m3/sec), moderate in MDZ (0.0045 m3/sec) and the lowest in HDZ (0.0032 m3/sec). Analysis of variance for water quality parameters (pH, NO2, NO3) revealed insignificant variations in relation to vegetation cover, whereas significant variations in alkalinity, total dissolved solids, conductivity and hardness were observed. In the light of these results, we concluded that the vegetation cover has close correlation with water and deforestation has significantly influenced water quantity and quality in the study area. Keywords: Deforestation, water quantity, water quality, vegetation zone, watershed, moist temperate forests.